China and Europe in 21st century global politics : partnership, competition or co-evolution - Austermann, Frauke; Vangeli, Anastas (Cambridge Scholars Publishing, 2013)
"China and Europe both decisively shape twenty-first century global politics. Successful cooperation between Europe and China continues, notably in climate change mitigation, or finding a way out of the financial crisis. Relations are also increasingly institutionalised, such as through Summits or High-level Dialogues. However, although in 2013 the EU and China have celebrated the 10-year-anniversary of their Strategic Partnership, struggles have re-emerged in relation to human rights, intervention in crisis regions such as Syria, and trade subsidisation and protectionism in areas such as the solar energy industry"--Jacket